01.08 Metabolic symbiosis between cells of the inflamed joint. (1st March 2017) - Sahota, Kalvin; Fitzpatrick, Martin; Filer, Andrew; Falconer, Jane; Young, Stephen P
Abstract : Background: Metabolism underlies the function of all cells, and this is particularly true of the musculoskeletal system with its high energy requirements for normal function of muscle and maintenance and growth of bones. In disease, energy requirements are even greater, with the whole body metabolic rate being around 10% higher in a rheumatoid arthritis patient compared to a healthy control. Objectives: To understand the metabolic perturbations in RA we have investigated the metabolomics of synovial fibroblasts and the major infiltrating immune cells in the joint, T lymphocytes and macrophages. Methods: Synovial fibroblasts were grown from biopsies of early and established RA, and CD4 lymphocytes and M1 and M2 macrophages were derived from healthy control blood. Metabolites in cell extracts were identified using NMR spectroscopy and lymphocyte metabolic flux assessed using the Seahorse metabolic flux analyser. Results: Synovial fibroblasts from RA were glycolytically active compared to normal cells, consuming glucose and producing lactate. Lactate applied exogenously to macrophages induced substantially higher IL6 production following LPS stimulation. Furthermore, IL6 exposure of CD4 T cells prior to antiCD3/CD28 activation promoted glycolysis and enhanced proliferation. Conclusion: We suggest a unique metabolic symbiosis may exist between the major cells involved in RA pathogenesis which may augment and reinforce their function and thus the chronic inflammatory destructive processes involved in RA.